Anonymizing witnesses in Federal Law No. (14) of (2020 AD) Concerning the protection of witnesses and the like - Almarzooqi, Rashed Abdulla Ahmed Faridi (Journal of Economic, Administrative and Legal Sciences, 2023)
Witnesses are one of the soldiers in achieving justice, and they have a fundamental role in establishing the values of criminal justice, because of the service they provide to society and the judiciary by giving testimony.While the legal status of the witness is of great importance in various legislations, which have required the protection of witnesses, in order to reduce the threats that may befall them or those closely related to them, and with that importance, we find that most of the legislations have set objective, procedural and security frameworks and measures for them, the most important of which was the measures of anonymity of the witness.The researcher used the descriptive and analytical approach, by studying and analyzing the provisions of Federal Law No. (14) Of (2020 AD) regarding the protection of witnesses and their equivalents, and the comparative approach whenever possible, in order to search for comparative laws in the subject of the study. The study concluded that the UAE legislator has agreed to a large extent, in its provision to obscure the witness as one of the protection measures in Federal Law No. (14) of (2020) regarding the protection of witnesses and their equivalents, it has specified the necessary measures to obscure witnesses and their equivalents, whether as protection measures outside or during trial procedures, and that The UAE legislator has permitted in Federal Law No. (14) Of (2020) regarding the protection of witnesses and those in their status to make witnesses anonymous by using modern technologies to hear their testimony from a distance.
Keywords: federal law; UAE; ignoring witnesses; witness protection